Inheritance of protein percentage in rice grain (review) - P. I. Kostylev; E. V. Krasnova; E. V. Dubina (Зерновое хозяйство России, 2025)
Rice cereal is an important food product all over the world, especially in Asia. White rice is usually used, but brown rice without outer hull is much healthier. The pericarp of rice grains contains proteins that increase immunity and protect the body from cardiovascular diseases and cancer, which has increased the relevance of this issue. The current paper has presented a review of the papers on the inheritance of quantitative trait loci responsible for protein percentage in rice grain. The study was conducted in India, China, Korea and Japan using dihaploid and recombinant inbred lines from hybrids obtained from rice varieties with various protein percentage. Due to DNA markers, there have been identified QTL which control protein percentage in rice chromosomes. The researchers from Asia have identified between 2 and 22 QTL that have been mapped onto chromosomes. Genomic analysis has identified QTL that control the synthesis of various protein fractions, such as albumin, prolamin, globulin, and glutenin. Hu et al. (2004) found three QTL of oil on chromosomes 1, 2, and 5. Yu et al. (2009) found four QTL on chromosomes 3, 5, 6, and 8. Qin et al. (2010) mapped eight QTL on chromosomes 1, 2, 3, 5, 6, 7, and 9. Kim et al. (2013) found a significant QTL, qRLC5, on chromosome 5. Yun et al. (2014) found that high lipid content was determined by three QTL on chromosomes 2, 3, and 6. Ying et al. (2012) identified 29 QTL on 10 chromosomes, several for seven fatty acids. Zhou et al. (2021) conducted a genomic study of oil composition and concentration in different groups of 533 cultivated rice varieties and identified 99 QTL, 94 of which were associated with oil composition and five with oil concentration. Tan et al. (2001) found that protein percentage was affected by two QTL on chromosomes 6 and 7. Hu et al. (2004) found five major QTL for protein percentage, located on chromosomes 1, 4, 5, 6, and 7. Yu et al. (2009) identified five QTL on chromosomes 3, 5, 6, and 10. Zhang et al. (2008) identified and mapped 16 QTL for four protein fractions on eight chromosomes. Zheng et al. (2011) identified 10 unconditional QTL significantly affecting protein percentage on nine chromosomes. Yun et al. (2014) found that high protein percentage was determined by three QTL on chromosomes 8, 9, and 10. Zhao et al. (2022) found 22 QTL affecting protein percentage on all chromosomes except chromosome 1. These QTL can be used by marker-assisted selection to pyramid favorable alleles in a single genotype to develop varieties with improved rice grain quality.